Persepsi Petani Milenial Terhadap Sistem Hidroponik Nutrient Film Technique (NFT) pada Budidaya Sayuran di Desa Suci - Anisa Khoiriyatul Ma'rifah; Diah Puspaningrum; Aryo Fajar Sunartomo; Beta Rianul Setiawati (AGRIBIOS, 2026)
Nutrient Film Technique hydroponics is one of the village programmes to maintain food security in Suci Village. The existence of NFT hydroponics can overcome land limitations and increase the interest of millennial farmers. The implementation of this hydroponics is supported by BUMDes, PKK, Destana and academics to manage hydroponic vegetables. This study aims to analyse the perception process of millennial farmers towards the NFT hydroponic system in vegetable cultivation in Suci Village. The theories used are the perception process according to Pareek (1996) and innovation characteristics according to Rogers (2003). This study uses a qualitative descriptive method with two triangulations, namely source triangulation and technique triangulation. Data collection methods in this study included observation, interviews, and documentation. The results of the study indicate that millennial farmers' perceptions of NFT hydroponics are greatly influenced by experience, motivation, and support from the surrounding environment. Positive perceptions felt by farmers include that hydroponic vegetables have good quality and serve as an alternative solution to address land constraints. Meanwhile, negative perceptions are related to high initial capital costs, lack of knowledge in managing the hydroponic system, absence of a specialised market, and complex maintenance. This indicates that the level of acceptance of hydroponics is closely related to the innovation characteristics perceived by farmers in determining how quickly or slowly an innovation is adopted, thus requiring guidance and education.